Warped extra dimension and inclined events at Pierre Auger Observatory - Kisselev Alexander; Shkalina Liliya (EPJ Web of Conferences, 2016)
The generalized solution for the warp factor of the Randall-Sundrum metric is presented which is symmetric with respect to both branes and explicitly periodic in extra variable. Given that the curvature of the 5-dimensional space-time is small, the expected rate of neutrino-induced inclined events at the Surface Detector of the Pierre Auger Observatory is calculated. Both the “downward-going” (DG) and “Earth-skimming” (ES) neutrinos are considered. By comparing the expected event rate with the recent Auger data on searching for neutrino candidates, the lower bound on the fundamental gravity scale M5 is obtained. The ratio of the number of the ES air showers to the number of the DG showers is estimated as a function of M5.